Biotinidase deficiency mimicking neuromyelitis optica: Initially exhibiting symptoms in adulthood. (October 2015) - Bottin, Laure; Prud'hon, Sabine; Guey, Stéphanie; Giannesini, Claire; Wolf, Barry; Pindolia, Kirit; Stankoff, Bruno
Background: Children with untreated biotinidase deficiency can experience variable symptoms depending on their age of presentation. Older children and adolescents can exhibit predominant neurological deficits including para- or tetraparesis and vision loss. Methods: We report the first case of delayed-onset biotinidase deficiency in a young adult. Results: A 22-year-old man presented with a disabling extensive myelopathy and bilateral optic neuropathy which mimicked the findings of a (seronegative) neuromyelitis optica. Imaging investigations were characterized by an MRI T2 hyper-intensity involving the spinal cord, the optic nerves, the fornix and the mammillar bodies, together with an increased 18 F-FDG uptake on positron emission tomography. He was ultimately shown to have profound biotinidase deficiency due to a novel missense mutation and was partly improved by oral biotin therapy. Conclusion: This individual exemplifies the need to include biotinidase deficiency in the differential diagnosis of patients with extensive myelopathy and/or bilateral optic neuropathy and argues for newborn screening for the disorder.